Find the difference quotient of \( f \), that is, find \( \frac{f(x+h)-f(x)}{h}, h \neq 0 \), for the following function. \( f(x)=-4 x+6 \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To find the difference quotient, we first need to compute \( f(x+h) \). Given the function \( f(x) = -4x + 6 \): 1. Calculate \( f(x+h) \): \[ f(x+h) = -4(x+h) + 6 = -4x - 4h + 6 \] 2. Now, plug this back into the difference quotient formula: \[ \frac{f(x+h) - f(x)}{h} = \frac{(-4x - 4h + 6) - (-4x + 6)}{h} \] 3. Simplify the numerator: \[ = \frac{-4x - 4h + 6 + 4x - 6}{h} = \frac{-4h}{h} \] 4. Finally, since \( h \neq 0 \), we can cancel \( h \) to find: \[ = -4 \] So, the difference quotient for the function \( f(x) = -4x + 6 \) is \( -4 \).